Analyzing Students’ Mathematical Representation Skills in Probability Based on Learning Style Variations - Fatkhunur Fariza Rahmadiansyah; Imam Sujadi; Ikrar Pramudya (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: Describe the mathematical representation of each student's learning style in solving probability material problems. The research form used is qualitative research. The subjects of the study were students of class VIII A of SMPN 3 Ngawi who had studied probability topic. The research data came from written tests and interviews. Subjects with visual learning style have sufficient ability in word representation, less in visual representation, both in pictorial and symbolic representation. Subjects with auditory learning style have sufficient ability in word and symbolic representation, both in visual and pictorial representation. Subjects with read/write learning style have insufficient ability in word representation, both in visual representation, sufficient in pictorial and symbolic representation. Subjects with kinesthetic learning style have sufficient ability in word, visual and pictorial representation and less in symbolic representation. Keywords: mathematical representation, probability, learning style.